The Controversial Role of Irisin in Clinical Management of Coronary Heart Disease - Ou-Yang, Wen-Lu; Guo, Bei; Xu, Feng; Lin, Xiao; Li, Fu-Xing-Zi; Shan, Su-Kang; Wu, Feng; Wang, Yi; Zheng, Ming-Hui; Xu, Qiu-Shuang; Yuan, Ling-Qing (Frontiers in Endocrinology, 2021)
Irisin, a PGC1α-dependent myokine, was once believed to have beneficial effects induced by exercise. Since its first discovery of adipose browning in 2012, multiple studies have been trying to explore the metabolic functions of irisin, such as glucose and lipid metabolism. However, recently many studies with irisin concentration measuring were doubt for methodological problems, which may account for the continuous inconsistencies. New tools like recombinant irisin and gene-knockout mice are required to reconfirm the questioned functions of irisin. In this paper, we make a critical introduction to the latest researches concerning the relationship between irisin and coronary heart disease, which includes atherosclerosis, stable angina pectoris and acute coronary syndromes. These studies provided various controversial evidence of short and long-term monitoring and therapeutic effect from molecular cellular mechanisms, in vivo experiments and epidemiological investigation. But with ambiguities, irisin still has a long way to go to identify its functions in the clinical management.